Control of the pattern-recognition receptor EFR by an ER protein complex in plant immunity - Nekrasov, Vladimir (Nature Publishing Group, 2009)
In plant innate immunity, the surface-exposed leucine-rich repeat receptor kinases EFR and FLS2 mediate recognition of the bacterial pathogen-associated molecular patterns EF-Tu and flagellin, respectively. We identified the Arabidopsis stromal-derived factor-2 (SDF2) as being required for EFR function, and to a lesser extent FLS2 function. SDF2 resides in an endoplasmic reticulum (ER) protein complex with the Hsp40 ERdj3B and the Hsp70 BiP, which are components of the ER-quality control (ER-QC). Loss of SDF2 results in ER retention and degradation of EFR. The differential requirement for ER-QC components by EFR and FLS2 could be linked to N-glycosylation mediated by STT3a, a catalytic subunit of the oligosaccharyltransferase complex involved in co-translational N-glycosylation. Our results show that the plasma membrane EFR requires the ER complex SDF2–ERdj3B–BiP for its proper accumulation, and provide a demonstration of a physiological requirement for ER-QC in transmembrane receptor function in plants. They also provide an unexpected differential requirement for ER-QC and N-glycosylation components by two closely related receptors.